Brushed under the carpet: Examining the complexities of participatory research. (12th September 2019) - Lenette, Caroline; Stavropoulou, Nelli; Nunn, Caitlin; Kong, Sui Ting; Cook, Tina; Coddington, Kate; Banks, Sarah
Abstract : Participatory research is sometimes difficult and risky, but there is a paucity of opportunities – and some reluctance – to reflect on its challenging aspects. In this article, we present subjective accounts of our everyday experiences of conducting participatory research as women researchers. We focus on four themes from our combined research experiences to explore some of the frustrations we encounter in participatory research. We argue that it is crucial to identify, reflect upon and address such aspects in academic outputs to broaden debates and scholarly discussions. We offer these reflections, and related strategies, as a contribution to critical debates on participatory research practice.